MYOPIA AND ITS COMPLICATIONS - Fayzullayeva Gavhar Jamoljonovna (KONFERENSIYALAR, 2025)
Аnnotation.  This  review  explores  current  views  on  the  causes  and development  of  complications  related  to  myopic  refraction.  It  summarizes domestic and international research using modern diagnostics and highlights that myopia involves not only refractive and anatomical changes, but also pathological processes linked to disrupted ocular hemodynamics and hydrodynamics.